2006
DOI: 10.1002/sia.2311
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of kaolin spheres produced by a gel‐casting process with a biopolymer additive

Abstract: Over the past few years due to increased environmental awareness, there has been great interest in improving ceramic processing to reduce the use of organic solvent and synthetic binders. This work is focused on a gel-casting process using a biopolymer that is environmentally friendly, easy to burn out and inexpensive. Starch was employed as a binder and kaolin clay was used as the starting material. To fabricate kaolin spheres, aqueous kaolin slurry was mixed with a starch solution. A small volume of the kaol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Origin of agglomerates can be due to incomplete dispersion of ceramic particle or incomplete dissolution of gelling agent in the solvent medium. Chumnanklang et al 32 reported that for higher starch content, the gelled starch occupies a larger space between the particles.…”
Section: Resultsmentioning
confidence: 98%
“…Origin of agglomerates can be due to incomplete dispersion of ceramic particle or incomplete dissolution of gelling agent in the solvent medium. Chumnanklang et al 32 reported that for higher starch content, the gelled starch occupies a larger space between the particles.…”
Section: Resultsmentioning
confidence: 98%
“…The results showed that porosity linearly increased with increasing starch content. According to Chumananklang et al [11], the gelled starch with higher starch content occupies a larger space between particles. Larger pores cannot be eliminated after the binder burnout step and hence results in a higher porosity.…”
Section: Resultsmentioning
confidence: 99%